Clinical and echocardiography predictors of response to inhaled nitric oxide in hypoxic preterm neonates. (8th December 2018) - Ahmed, Mohamed Shalabi; Giesinger, Regan E; Ibrahim, Mohamed; Baczynski, Michelle; Louis, Deepak; McNamara, Karl P; Jain, Amish; Weisz, Dany E; McNamara, Patrick J
Abstract : Aim: To evaluate the clinical and echocardiography modulators of treatment response in hypoxemic preterm infants exposed to inhaled nitric oxide (iNO). Methods: In this multicentre retrospective study, clinical parameters, including oxygenation, ventilation and haemodynamics, were collected for preterm infants <36 weeks gestation before and 2 h after initiation of iNO for acute hypoxemia. Comprehensive echocardiography, performed near the time iNO initiation, was analysed by experts blind to the clinical course. Multiple logistic regression analysis was used to identify factors associated with iNO response as defined by a reduction in the fraction of inspired oxygen by >0.20. Results: A total of 213 infants met eligibility criteria, of which 73 had echocardiography data available and formed the study cohort. Response to iNO was demonstrated in 56% of patients. Younger post‐natal age (odds ratio (OR) 0.94; 95% confidence interval (CI) 0.89, 0.99) and the presence of pulmonary hypertension (PH) (OR 4.47; 95% CI 1.23–11.9) were independently predictive of iNO response regardless of gestational age. Among neonates <72 h old with documented PH, iNO response was seen in 82%. The onset of a new diagnosis of severe (grade III/IV) intraventricular haemorrhage (IVH) after iNO treatment was seen in 6 of 40 patients <28 weeks' gestational age, with a greater frequency in responders (32 vs. 0%, P  = 0.02). Conclusions: Positive response to iNO is greatest in the first 3 days of life and in patients with echo‐confirmed PH, independent of gestational age. The association between critical illness, iNO administration and IVH in extremely premature infants may merit prospective delineation.